2022
DOI: 10.1080/18335330.2022.2108331
|View full text |Cite
|
Sign up to set email alerts
|

The use of self-disclosure to build rapport with mock covert human intelligence sources (CHIS)

Abstract: The use of covert human intelligence sources for the protection of national security is an important but under-researched area. In light of increased globalisation, and technological developments, examining covert intelligence gathering online may have operational relevance. This study examined the use of similarities in self-disclosure to develop rapport with mock covert human intelligence sources online. A sample of 66 participants were asked to assume the role of a CHIS, listen to an audio recording of a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Nunan et al (2020d) conducted a field study of handlers and informants examining the relationship between rapport and information, and whilst they found a direct relationship between rapport and intelligence yield there are a number of other potentially confounding variables (such as length of relationship, nature of tasking, value of intelligence) that were unreported and which might correlate to both rapport and information. Indeed, Marin and Gabbert (2022) found that handlers were able to increase rapport with mock-informants through the use of self-disclosure, but this did not translate into greater intelligence yield; it is perhaps noteworthy that in their study, Marin and Gabbert controlled for cooperation by informing participants to strike a balance between being forthcoming whilst remaining loyal to their criminal associates. As such, the influence of rapport on the amount of information gathered from an informant is unclear and remains an understudied area of research.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Nunan et al (2020d) conducted a field study of handlers and informants examining the relationship between rapport and information, and whilst they found a direct relationship between rapport and intelligence yield there are a number of other potentially confounding variables (such as length of relationship, nature of tasking, value of intelligence) that were unreported and which might correlate to both rapport and information. Indeed, Marin and Gabbert (2022) found that handlers were able to increase rapport with mock-informants through the use of self-disclosure, but this did not translate into greater intelligence yield; it is perhaps noteworthy that in their study, Marin and Gabbert controlled for cooperation by informing participants to strike a balance between being forthcoming whilst remaining loyal to their criminal associates. As such, the influence of rapport on the amount of information gathered from an informant is unclear and remains an understudied area of research.…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, the RWITS-US model was designed to increase relational rapport between handler and informant. The welfare phase was designed to provide the informant with a sense of autonomy, whilst presenting the handler with an opportunity to demonstrate concern through the use of interpersonal skills, such as active listening and appropriate self-disclosures (Hargie & Dickson, 2004;Marin & Gabbert, 2022). The handlers concern for the informants welfare was re-iterated during the security phase at the close of the interview.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crough et al (2022) noted that their definition precisely explicated the nature of rapport in investigative interviewing. Others mentioned that their definition is synonymous with rapport (Marin & Gabbert, 2022); is considered to be rapport (Foster et al, 2022); and the typical or a complete description of rapport.…”
Section: Resultsmentioning
confidence: 99%